2016
DOI: 10.1016/j.euroecorev.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Author׳s gender affects rating of academic articles: Evidence from an incentivized, deception-free laboratory experiment

Abstract: In this study we sought to verify the hypothesis that a researcher's gender affects evaluation of his or her work, especially in fields in which women are a small minority. To this end we asked a sample of economics majors to rate papers written by mixed-gender couples, indicating that they were (co-) authored by a "female economist", "male economist", "young female economist" or "young male economist". While the age factor played no role, female authors received lower ratings. This effect was independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 39 publications
0
53
3
Order By: Relevance
“…; Knobloch‐Westerwick, Glynn & Huge ; Krawczyk & Smyk ), but a few find evidence that works authored by women are rated lower. For example, students rated conference abstracts with male authors to be of greater scientific quality (Knobloch‐Westerwick, Glynn & Huge ), and rated economics papers authored by men as more publishable (Krawczyk & Smyk ; though economics as a field may be more male‐biased than the biological sciences, van Arensbergen, van der Weijden & van den Besselaar ). Overall, though gender biases are clearly evident in many aspects of academic research and careers (e.g., recruitment of editors, symposium participation invitations, evaluation of academic job applicants; Moss‐Racusin et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Knobloch‐Westerwick, Glynn & Huge ; Krawczyk & Smyk ), but a few find evidence that works authored by women are rated lower. For example, students rated conference abstracts with male authors to be of greater scientific quality (Knobloch‐Westerwick, Glynn & Huge ), and rated economics papers authored by men as more publishable (Krawczyk & Smyk ; though economics as a field may be more male‐biased than the biological sciences, van Arensbergen, van der Weijden & van den Besselaar ). Overall, though gender biases are clearly evident in many aspects of academic research and careers (e.g., recruitment of editors, symposium participation invitations, evaluation of academic job applicants; Moss‐Racusin et al .…”
Section: Discussionmentioning
confidence: 99%
“…) but primarily in the health sciences and other fields (Lane & Linden ; Heckenberg & Druml ; Walker et al . for manuscript review; Dickson ; Grant, Burden & Breen ; Friesen ; Ley & Hamilton ; Leemann & Stutz ; Sandström & Hällsten ; Marsh, Jayasinghe & Bond , ; Mutz, Bornmann & Daniel for grant reviews), generally find that peer review is gender neutral, though there are some exceptions (e.g., Knobloch‐Westerwick, Glynn & Huge ; Krawczyk & Smyk ). However, most manipulative studies use student populations as their raters, and the majority of analyses of peer review done by professional researchers look at grant applications; few have looked at manuscript submissions to academic journals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the frequency and degree to which peer review of scholarly manuscripts and grant proposals discriminates against women remains a subject of significant debate. Some experimental studies, in which author genders are manipulated (e.g., investigators manipulate the gender of names on author bylines), have found that papers with male-sounding author names are rated more highly than those with female-sounding names (Knobloch-Westerwick, Glynn, & Huge, 2013;Krawczyk & Smyk, 2016), though there are exceptions (Borsuk, Budden, Leimu, Aarssen, & Lortie, 2009). In contrast, correlational studies of manuscript or grant review commonly find it to be gender neutral (e.g., no discrepancy in outcomes between papers with male vs. female authors; Buckley, Sciligo, Adair, Case, & Monks, 2014;Edwards, Schroeder, & Dugdale, 2018;Fox, Burns, Muncy, & Meyer, 2016;Heckenberg & Druml, 2010;Lane & Linden, 2009;Primack, Ellwood, Miller-Rushing, Marrs, & Mulligan, 2009 for manuscript review; Cañibano, Otamendi, & Andújar, 2009;Leemann & Stutz, 2008;Ley & Hamilton, 2008;Marsh, Jayasinghe, & Bond, 2008;Marsh, Jayasinghe, & Bond, 2011;Mutz, Bornmann, & Daniel, 2015;Reinhart, 2009;Sandström & Hällsten, 2008, and references therein, for grant reviews), though there are exceptions in which men (Kaatz et al, 2016;Ledin, Bornmann, Gannon, & Wallon, 2007;Murray et al, 2018;Walker, Barros, Conejo, Neumann, & Telefont, 2015) or women (Lerback & Hanson, 2017) have higher success rates.…”
Section: Introductionmentioning
confidence: 99%
“…To name a few, female academics are less likely to receive grant funding 7 , less likely to win prizes 8 , more likely to be seen as less competent than males 9 , and more likely to have their gender misattributed in publications 10 . They also often end up taking on more teaching and administrative duties than their male colleagues; this work is rarely appropriately recognised by promotion or hiring boards.…”
mentioning
confidence: 99%